An update on the ayurvedic herb Centella asiatica - Dsouza, Vinisha Seema (Indian Journal of Pharmacy & Drug Studies, 2023)
Plants have been demonstrated extraordinary source of medicine and recently focus on medicinal plant research has increased. For its traditional usage and medical benefits in the treatment of numerous ailments, Centella asiatica is widely known. The utilization of this plant as a whole and isolated bioactive chemical are both commonly employed to cure a variety of human illnesses, according to published research. According to reports, Centella asiatica has a range of pharmacological properties, including antibacterial, anticancer, wound-healing, neuroprotective, immunomodulatory, anti-inflammatory, hepatoprotective, insecticidal, and antioxidant properties. Asiatic acid, asiaticosside, and madecassoside are among the several flavonoids and terpenoid chemicals found in Centella asiatica, each of which is known for its pharmacological importance. The significant medicinal plant Centella asiatica is identified and described as bioactive components, pharmacological characteristics, in vitro propagation, and traditional usage was all succinctly covered in the present review.